Residue depletion laws of florfenicol and its metabolite florfenicol amine in eggs - ZHANG Jing; ZHOU Qian; GAO Yushi; TANG Xiujun; LU Junxian; MA Lina; CHEN Dawei; TANG Mengjun (浙江大学学报. 农业与生命科学版, 2021)
A study on florfenicol (FF) and florfenicol amine (FFA) residue depletion raws was conducted in eggs. After the chickens were administered successively florfenicol (FF) powder of 15 mg/kg (prevention group) and 30 mg/kg (treatment group) of body mass in the form of premix for 5 d, the eggs of each group were collected at administration period and 1, 2, 3, 5, 7, 10, 12, 15, 18 d at withdrawal period. Then FF and FFA residues of egg, egg yolk and egg white were detected using high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The results showed that the limits of detection (LOD) of FF and FFA in egg, egg yolk and egg white were 2 μg/kg, and the limits of quantitation (LOQ) were 5 μg/kg. The average recoveries were in the range of 78.9%-105.0% when the egg samples were added with FF in the range of 1.0-5.0 μg/kg, and the intraday precision and the interday precision was 2.22%-4.22% and 4.22%-6.54%, respectively. The peak values of FF residues (520.70, 797.12 μg/kg) of egg white in prevention group and treatment group, respectively, were higher than those of egg yolk (285.96, 442.40 μg/kg), while the peak values of FFA residue (218.40, 646.14 μg/kg) of egg yolk in prevention group and treatment group, respectively, were higher than those of egg white (87.36, 36.89 μg/kg). The elimination rates of FF and FFA in egg white were faster than those in egg yolk. FF and FFA residues and their total residues were positively correlated with the dosage. FF and FFA mainly existed in the egg yolk, and FF mainly existed in the egg white. The FF residual time of egg yolk in different dosage groups was 18 d.